2019
DOI: 10.9770/ird.2019.1.3(3)
|View full text |Cite
|
Sign up to set email alerts
|

The role of SMEs development on poverty alleviation in Nigeria

Abstract: The role of SMEs development on poverty alleviation has been a core element of the current report. This study examined the role of small and medium enterprises on poverty eradication in Nigeria. Two research questions were posed for the study and two hypotheses formulated in line with the objectives. One hundred and forty two (142) questionnaires were administered randomly to the entire employee population of the SME companies that are registered with SMEDAN in Lagos Nigeria. The sample size was determined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Nowadays, these ideas for analysing and regulating income distribution are fundamental for the studies of living standards and economic processes caused by their changes. In particular, the noted studies analyse the links between income distribution and economic growth [20], including investment flows [21][22][23], income inequality, and current account imbalances [24,25]; indirect impact of some specific factors on income inequality [26][27][28], particularly tolerance for corruption [29]. Baradas and Lagoa [30] also investigate new trends in globalisation, including changes in education and business cycles, within the framework of the analysis of the impact of the financialization process on the labour force share in Gross domestic product (GDP) due to its impact on government activity and trade union density.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nowadays, these ideas for analysing and regulating income distribution are fundamental for the studies of living standards and economic processes caused by their changes. In particular, the noted studies analyse the links between income distribution and economic growth [20], including investment flows [21][22][23], income inequality, and current account imbalances [24,25]; indirect impact of some specific factors on income inequality [26][27][28], particularly tolerance for corruption [29]. Baradas and Lagoa [30] also investigate new trends in globalisation, including changes in education and business cycles, within the framework of the analysis of the impact of the financialization process on the labour force share in Gross domestic product (GDP) due to its impact on government activity and trade union density.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This empirical finding is supported by a study carried out by Manzoor et al (2019) through analysis with a data panel model in SAARC. Furthermore, Kowo, Adenuga, and Sabitu (2019), using analysis of variance, coefficient of correlation, and regression analysis, found that the development of SMEs influences poverty in Nigeria. However, it is contradicted by previous studies conducted by Beck, Demirguc-Kunt, and Levine (2005), which found that MSMEs did not affect the reduction of poverty in the 45 countries where they gathered research samples.…”
Section: Literature Surveymentioning
confidence: 99%
“…This study is in line with the one conducted by Agyapong (2010) on the cases of women working for MSEs in Ghana. Moreover, Kowo, Adenuga, and Sabitu (2019) point out that MSEs influence the reduction of poverty through the creation of job vacancies in Nigeria. Rotar, Pamić, and Bojnec (2019) also found that there is a significant correlation between MSEs and labor absorption in the service industry.…”
Section: Literature Surveymentioning
confidence: 99%
“…Kowo et al [30] examined the role of SMEs on poverty eradication in Nigeria. They used primary data for the analysis.…”
Section: Sme In Global Perspectivementioning
confidence: 99%